The behaviour of arcs in carbon mixed-mode high-power impulse magnetron sputtering - Tucker, Mark; Putman, Kate; Ganesan, R.; Lattemann, M.; Stueber, M.; Ulrich, S.; Bilek, M.; McKenzie, D.; Marks, Nigel (IOP Publishing Ltd, 2017)
Mixed-mode deposition of carbon is an extension of high-power impulse magnetron sputtering in which a short-lived arc is deliberately allowed to ignite on the target surface to increase the ionised fraction of carbon in the deposition flux. Here we investigate the ignition and evolution of these arcs and examine their behaviour for different conditions of argon pressure, power supply voltage, and current. We find that mixed-mode deposition is sensitive to the condition of the target surface, and changing the operating parameters causes changes in the target surface condition which themselves affect the discharge in a process of negative feedback. Initially the arcs are evenly distributed on the target racetrack, but after a long period of operation the mode of erosion changes and arcs become localised in a small region, resulting in a pronounced nodular structure. We also quantify macroparticle generation and observe a power-law size distribution typical of arc discharges. Fewer particles are generated for operation at lower Ar pressure when the arc spot velocity is higher.